Biochemistry : an introduction - Mckee, Trudy (WCB/McGraw-Hill, 1999)
Designed for a diverse audience, ranging from students of chemistry to the life sciences, this text discusses molecular structure and the role it plays in metabolism. It presents a review of basic biology, organic chemistry and general chemistry, and reflects DNA technology.